Analisis Media Framing Pemberitaan Media Organized Crime and Corruption Reporting Project (OCCRP) dalam Pemberitaan Joko Widodo Pemimpin Terkorup: Studi Pada Media Tempo.Com - Muhammad Asrul; Korry El Yana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the framing of Tempo.co's media coverage of the inclusion of the 7th President Joko Widodo as one of the finalists for the 2024 'person of the year' by the Organized Crime and Corruption Reporting Project (OCCRP), which highlights the world's most corrupt leaders. Using the framing theory of Zhongdang Pan and Gerald M. Kosicki, this study examines how syntactic, script, thematic, and rhetorical structures are used in the construction of news by tempo.co. The results of the study show that although OCCRP stated that it had no evidence of Joko Widodo's personal involvement in corruption, Tempo.co's reporting emphasized the issue of weakening the Corruption Eradication Commission (KPK) and allegations of political intervention for the benefit of the President's family. The framing used formed a critical public perception of Joko Widodo's leadership. This study shows the important role of media in shaping social construction and public opinion through the presentation of news that is structured and full of ideological meaning